STRATEGI KOMUNIKASI POLITIK WITA SUSILOWATY DALAM PEMILIHAN UMUM LEGISLATIF DPRD DKI JAKARTA TAHUN 2024 - Anindya Naylal Husna; Annisaa Dwi Astrid; Khilda Fatmawati; Nasywa Nurul Aini; Muhammad Prakoso Aji (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Wita Susilowaty is a young political figure who has successfully implemented effective political communication strategies in Indonesia’s democratic arena. She was elected as a legislative member in the 2019 General Election and re-elected in 2024. Her educational background in Communication and Information Technology from the Swiss German University has been a crucial foundation in designing adaptive communication strategies for Jakarta’s 10th Electoral District. This study applies Albert Bandura’s Persuasive Effect Theory, as outlined in Social Learning Theory (1977) and Social Foundations of Thought and Action: A Social Cognitive Theory (1986), to analyze Wita’s communication strategies through the process of observational learning, which includes four stages: attention, retention, reproduction, and motivation. Using a qualitative descriptive case study approach, this research aims to explore Wita Susilowaty’s political communication strategies during the 2024 Jakarta Legislative Election campaign. Data were obtained from two sources: primary data through in-depth interviews with Wita Susilowaty and secondary data from campaign documentation. The findings indicate that Wita employed a hybrid communication strategy, combining 70% conventional methods such as canvassing and grassroots visits (blusukan) with 30% social media engagement. This approach allowed her to build emotional closeness with constituents while simultaneously expanding the reach of her political messages in the digital sphere. Through this hybrid strategy, Wita successfully maintained public trust and was re-elected as a member of the Jakarta Regional House of Representatives (DPRD) representing the 10th Electoral District in the 2024 General Election.